THE GROUP OF DISCUSSION: THEORY AND PRACTICE - Izcara Palacios, Simón Pedro (Libros UAT, 2019)
The discussion group is a technique of great fertility. In contrast to quantitative research, which requires extensive samples, with a small number of discussion groups an investigation can be carried out. A discussion group is a work meeting in which 4 and 12 people, often unknown, who present spaces of collective identification, interact verbally, until they reach basic positions of consensus around a specific question of inquiry. The conversational interaction is conducted by a moderator, whose task is to impel the discursive dynamics, and prevent it from overflowing a predetermined theme. The moderator determines the speech process, in the sense that it is up to him to give the voice to the participants, through the control of the turn of speech, and it is also he who decides when to abort a topic and move on to other. The over-participation is as negative as the silence of one of the members of the group. Therefore, the most difficult task of the moderator is to foster a relationship of symmetry, and create a climate of equality among the members of the group, which avoids the over-participation or withdrawal of any of the members of the group.